Evaluating relative heat stress in the Natura 2000 site Kras under different climate change scenarios - Davidović, Danijel (Revija za geografijo, 2024)
The study evaluates relative heat stress in the Natura 2000 site Kras under various climate change scenarios using Multiscale Geographically Weighted Regression (MGWR). Optical and thermal satellite imagery and five future air temperature scenarios were utilized to downscale thermal conditions and evaluate relative heat stress. Results indicate significant spatiotemporal variability in LST, with the southeastern region being particularly susceptible to elevated heat stress. Projections show an overall increase in heat stress due to climate change. The study emphasizes the need for spatially explicit analyses and adaptive strategies to mitigate heat stress impacts on ecosystems and human populations.
Keywords: daljinsko zaznavanje; land surface temperature; MGWR; NDVI; prostorsko modeliranje; remote sensing; spatial modelling; temperatura površja